EP214/#508 Outcomes and long-term follow-up by treatment type for patients with advanced-stage ovarian cancer managed at a tertiary cancer center. (4th December 2022) - Ehmann, Sarah; Shay, Kelly; Zhou, Qin; Iasonos, Alexia; Sonoda, Yukio; Gardner, Ginger; Roche, Kara Long; Zammarrelli, William; O'Cearbhaill, Roisin; Zivanovic, Oliver; Chi, Dennis
Abstract : Objectives: To perform a detailed analysis of all treatment given to patients with advanced-stage ovarian cancer at a tertiary cancer center from the time of diagnosis to death or minimum 5 years follow-up. Methods: Newly diagnosed, stage III-IV ovarian cancer patients who underwent upfront treatment at our institution between 01/01/2015 and 12/31/2015 were included. We reviewed electronic medical records for clinicopathological, treatment, and survival characteristics. Results: One hundred fifty-three patients were included; 88 (58%) had stage III and 65 (42%) stage IV disease. Median follow-up was 65.8 months (3.6–75.3). Eighty-nine patients (58%) underwent primary debulking surgery (PDS), 50 (33%) received neoadjuvant chemotherapy followed by interval debulking surgery (IDS), and 14 (9%) had no surgery (NSx) and were treated with chemotherapy alone. Median PFS (months) to first recurrence was: 26.2 (20.1–36.2) for PDS; 13.5 (12–15.1) for IDS; and 4.2 (1.1–5.8) for NSx (p<0.001). At time of first recurrence/progression, 80 (72.7%) were treated with chemotherapy, 28 (25.5%) underwent secondary cytoreductive surgery followed by chemotherapy, and 2 (1.8%) had no treatment. Four (4.9%) of 82 underwent tertiary cytoreductive surgery. Seven (4.6%) underwent palliative surgery for malignant bowel obstruction. Five-year OS was 53.2% (44.7–61) for the entire cohort and 71.5% (60.2–80) for PDS. Median OS was not reached for PDS or the entire cohort. Median OS was 41.7 (26.7–57.6) for IDS and 14.6 months (1.1–27.8) for NSx (p<0.001). Conclusions: Given that the 5-year OS rate compares favorably to that described in the literature, these data can be a useful reference for patient counseling, long-term planning, and future studies.